Strategies for Marketing Development of Shoe Products of PT. XYZ Using SWOT Analysis Method - Andina, Niyar (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Business growth must be accompanied by a good marketing strategy, at PT. XYZ is carried out in a qualitative descriptive manner, where some of the qualitative data obtained is then made quantitative using a weight and rating measurement scale which is usually used in carrying out SWOT analysis. The SWOT analysis method without industrial scale (TSI) was then used to examine this research. Based on research findings, the company has marketed its products using various marketing initiatives, including direct selling, personal selling, publicity, and advertising so that customers can find out more. Strategies that can be used to determine competitive strategies at PT. XYZ is a stable growth strategy. This means that PT. XYZ may implement a growth approach in the future, but only in stages according to the priority scale. Since there are not enough marketing employees assigned to visit clients, businesses must focus on the marketing component. This business will need to increase staff in the marketing division in the near future. Additionally, businesses should build a website as a marketing tool to advertise their services to potential clients.